2005
DOI: 10.1074/jbc.m412650200
|View full text |Cite
|
Sign up to set email alerts
|

Junctional Adhesion Molecule 1 Regulates Epithelial Cell Morphology through Effects on β1 Integrins and Rap1 Activity

Abstract: Here we have used small interfering RNA to investigate the effect of the loss of JAM1 expression on epithelial cell function. Consistent with our previous study, knockdown of JAM1 was observed to increase paracellular permeability in epithelial monolayers. Interestingly, knockdown of JAM1 also produced dramatic changes in cell morphology, and a similar effect was observed with expression of a JAM1 mutant lacking the putative homodimer interface. Further studies revealed that JAM1 knockdown decreased cell-matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
200
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(227 citation statements)
references
References 67 publications
21
200
3
Order By: Relevance
“…In in vitro studies, Rap1 has been reported to regulate integrin levels in epithelial cells (Mandell et al, 2005) as well as integrin activation in leukocytes (Reedquist et al, 2000). To verify these results in vivo, we determined the influence of JAM-A on ␤1 integrin protein levels and Rap1 activation in intestinal epithelial cells derived from JAM-A knockout mice.…”
Section: Jam-a/afadin Signal Through the Small Gtpase Rap1a To Regulamentioning
confidence: 93%
See 2 more Smart Citations
“…In in vitro studies, Rap1 has been reported to regulate integrin levels in epithelial cells (Mandell et al, 2005) as well as integrin activation in leukocytes (Reedquist et al, 2000). To verify these results in vivo, we determined the influence of JAM-A on ␤1 integrin protein levels and Rap1 activation in intestinal epithelial cells derived from JAM-A knockout mice.…”
Section: Jam-a/afadin Signal Through the Small Gtpase Rap1a To Regulamentioning
confidence: 93%
“…Recently, it was shown that decreased JAM-A expression results in reduced activation of the small GTPase Rap1 (Mandell et al, 2005;Severson et al, 2008). In in vitro studies, Rap1 has been reported to regulate integrin levels in epithelial cells (Mandell et al, 2005) as well as integrin activation in leukocytes (Reedquist et al, 2000).…”
Section: Jam-a/afadin Signal Through the Small Gtpase Rap1a To Regulamentioning
confidence: 99%
See 1 more Smart Citation
“…Of primary interest in our study is the TJ protein JAM-A, which has important functions in cellular adhesive processes including TJ assembly (Liang et al, 2000), cellular polarity (Ebnet et al, 2001), the regulation of cell morphology (Mandell et al, 2005), angiogenesis (Cooke et al, 2006), platelet activation (Babinska et al, 2002) and leukocyte migration (Ostermann et al, 2002). We (McSherry et al, 2009) and others (Murakami et al, 2011) recently identified a significant association between JAM-A over-expression and poor prognosis of breast cancer patients.…”
Section: Introductionmentioning
confidence: 89%
“…65e67 An interesting feature of this family of proteins are the tissue-specific functions that seem to be governed by protein distribution patterns and may account for the wide variety of observed functions attributed to various JAMs. A few of the reported functions include regulation of epithelial barrier, 68,69 endothelial and epithelial cell migration, 70,71 spermatogenesis, 72 angiogenesis, 73 and leukocyte adhesion. 74 In addition, JAMs have been linked to roles in the pathophysiology of several disease processes, such as atherosclerosis, 75,76 cancer metastasis, 77 and IBD.…”
Section: Neutrophils Engage Basolateral Epithelial Receptors During Tmentioning
confidence: 99%